Purulent Renal Papillitis Due to Streptococcus Infantarius Subsp. Infantarius in a Horse - Eroksuz, Yesari; Otlu, Baris; Yerlikaya, Zeynep; Tanriverdi, Elif Seren; Incili, Canan Akdeniz; Karabulut, Burak; Eroksuz, Hatice (Sciendo, 2022)
A 6-year-old, male Arabian crossbred horse was necropsied after a 10 day history of loss of appetite, debility and weight loss. Gross and histologic examination was consistent with purulent papillitis due to Streptococcus infantarius subsp. infantarius. The isolate was sensitive to all the antibiotics tested.
PURULENTNI RENALNI PAPILITIS KOD JEDNOG KONJA USLED PRISUSTVA STREPTOCOCCUS INFANTARIUS SUBSP. INFANTARIUS
Keywords: Horse; equine; Streptococcus infantarius subsp; infantarius; pyelitis; early hepatic cirrhosis